IDP- Balco Enterprise collaboration program (Mac2021 - July2021) / Mohamad Zain Hashim - Hashim, Mohamad Zain (Unit Penerbitan FKAPP, 2021)
Infrastructure Design Project (IDP) (CEC594) course is designed to describe the synthesis of structural and infrastructure engineering fundamentals into an integrated and systematic analysis and design processes that would enable students to tackle complex engineering problems associated to a real-world construction project effectively and comprehensively. Emphasis is however given to infrastructural aspect of the engineering problem and solution such as earthworks, road and drainage, water supply network, and sanitary and sewerage network. This subject also involves many elements of program outcomes that need to be achieved by students, namely Engineering knowledge (PO1), Design/Development of solutions, Modern tool usage (PO5), The engineer & society (PO6), Individual & Team work (PO9) and Project Management & finance (PO11). The initiative will be driven by the need to add new knowledge to students in their final year who will graduate. Balco Enterprise proposes the use of CivilStar software for free to students who take the IDP subject. The CivilStar software offering contains several modules, namely TerraAlpha (earthwork design), TerraDrain (drainage design), TerraSewer (sewerage design) and TerraWater (water supply design).